The Illusion of Appellate Review in Dependency Proceedings. (March 2017) - LeVezu, Alicia
Abstract: In the realm of state trial courts, child abuse and neglect (dependency) proceedings are unique. Dependency proceedings place courts in the position, not of determining an ultimate result, but of overseeing the ongoing actions of a state agency. The court proceedings can continue on up to twenty‐one years without a culminating trial. We must revise our rules of appellate procedure to protect review of dependency decisions so that children and families have the access to justice they deserve.